Adapted DLC coatings for increasing tapping performance in TiAl6V4. Issue 8 (19th August 2013) - Klocke, F.; Gerschwiler, K.; Schiffler, M.; Morstein, M.; Dessarzin, P.; Lung, D.; Frank, H.
Abstract This paper reports on a new DLC‐coated high speed steel tool for tapping into TiAl6V4. In analogy tests on a high‐temperature tribometer, a comparative analysis was carried out on coating systems containing carbon, nitrides and oxides with respect to their suitability for tapping into TiAl6V4. This comparative analysis revealed that DLC coatings were characterized by extremely low friction coefficients, low levels of wear and low material adhesion. Cutting tests using high speed steel taps coated with the DLC coating system CROMTIVIc2 confirm the outstanding tribological properties of this coating system. Compared to conventional TiCN‐coated taps, the new DLC‐coated tool expands the current application field to include higher cutting speeds and longer tool life. It therefore provides the opportunity for significantly increasing productivity when tapping into TiAl6V4.